Vida útil e qualidade de duas espécies de hortaliças não convencionais: capuchinha (Tropaeolum majus L.) e ora-pro-nobis (Pereskia aculeata Miller) - Lima, Isadora Cardoso e (2017)
Eating healthy has been the subject of much research in several areas of knowledge and, with greater access to information, people have shown interest in and concern about healthy eating habits. The intake of fruits and vegetables is fundamental for the improvement of the population's health. Several investigations demonstrated the protective effect of fruits and vegetables for noncommunicable diseases. According to the following study, the consumption of fruits and vegetables can be stimulated by non-conventional or traditional vegetables, which are nutritionally enriched nosh that have already been widely appreciated, but are gradually forgotten or devalued, such as the nasturtium flower (Tropaeolum majus L.) and the ora-pro-nobis (Pereskia aculeata Miller). Two species of non-conventional vegetables, the nasturtium flower and the leaves and stems of ora-pro-nobis were analyzed. The first experiment aimed to study the shelf life of different colors nasturtium (red, orange, yellow, and light yellow) stored under refrigeration (5°C ± 2 and 85% ± 5 of RH) for 8 days. Initially, the freshly harvested nasturtium flowers were assessed, quantifying vitamin C, phenolic compounds, and carotenoids. Hereafter, physical and chemical characteristics (appearance, loss of mass, L*, C*, and, °H parameters, soluble solids, and titratable acidity) were analyzed every two days for 8 days of storage. A completely randomized design (CRD) was applied in a 4 x 5 factorial design, including two factors which were nasturtium color (red, orange, yellow, and light yellow) and storage time (0, 2, 4, 6, and 8 days), with five replications. The results showed that there is higher amount of vitamin C and phenolic compounds in the red nasturtium than in the other colors, and the yellow nasturtium showed the highest content of carotenoids. It was also found that the yellow and orange flowers had a longer shelf life compared to the red and light yellow flowers after 8 days of storage. In the second experiment the goal was to investigate the shelf life of the leaves and stems of five clones of ora -pro-nobis, assessing the physical and chemical characteristics (appearance, loss of mass, L*, C*, and °H parameters, chlorophyll a and b, total phenolic compounds, and vitamin C) of the stems at 5 times (0, 2, 4, 6, and 8 days) and the leaves at 7 times (0, 2, 4, 6, 8, 10, and 12 days) under cold storage (10°C ± 2 and 85% ± 5 of RH). The ora-pro-nobis leaves showed higher level of phenolic compounds and vitamin C compared to the stems. The results showed that the leaves had a longer postharvest life compared to the stems, keeping their integrity for a longer time.